Understanding the relationship between business and IT groups: a personal construct theory approach. (29th December 2006) - Fernando, Senaka; Lycett, Mark; De Cesare, Sergio
The relationship between business and Information Technology (IT) groups in organisations has consistently ranked as an important concern among business and IT managers. As a result, several researchers have investigated the means of improving the business/IT relationship. They focus on behaviours of business and IT groups and attempt to develop change management programmes as a vehicle for obtaining desired behaviours from business and IT groups in order to improve the 'relationship'. However, research shows that such attempts have a low success rate in attaining an effective 'relationship'. This paper argues that the reason for this is that most researchers tend to focus on behaviours of people without an in-depth understanding of their cognition, which influences those behaviours. Consequently, the paper proposes a cognitive approach and explores the application of Personal Construct Theory (PCT) to understand the 'relationship' and means to improve it.